Global Research Trends and Regional Disparities in the Political Participation of Arab Muslim Migrants: A Bibliometric Analysis (2013–2023) - Darwis, Danial (JSP (Jurnal Ilmu Sosial dan ilmu Poltik), 2025)
This bibliometric analysis of Scopus-indexed literature (2013–2023) investigates global research trends and regional disparities in the political participation of Arab Muslim migrants. By analysing 12 studies selected from 30 initial search results, the study identifies dominant themes such as diaspora, religiosity, and activism that reflect the socio-political dynamics of Arab Muslim migrants in host countries. These findings highlight the intersections between migration, identity, and politics, influencing policy and integration processes. However, notable regional disparities exist, with 75% of studies originating from the United States and Western Europe, while contributions from the Middle East and North Africa remain minimal. This imbalance limits perspectives and highlights underrepresentation. The research gaps also include insufficient exploration of how European policies affect integration and limited empirical studies addressing political participation strategies in non-Western contexts. This study emphasises the significance of political participation in fostering multicultural policy development and integration. The bibliometric methodology employed, including the use of VOSviewer for keyword co-occurrence analysis, provides quantitative insights into research patterns and thematic clusters, ensuring a rigorous evaluation of trends and gaps. Practical implications include the need for interdisciplinary and regionally inclusive approaches to address systemic barriers and enhance participation. Policymakers and researchers are encouraged to prioritise underrepresented themes and regions, facilitating more inclusive and comprehensive migration studies.